1994
DOI: 10.1042/bj3040569
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the single Ca2+-binding site on the Ca2+-ATPase reconstituted with short- or long-chain phosphatidylcholines

Abstract: On reconstitution of the Ca(2+)-ATPase of skeletal muscle sarcoplasmic reticulum into bilayers of dimyristoleoylphosphatidylcholine [di(C14:1)PC] or dinervonylphosphatidylcholine [di(C24:1)PC] the stoichiometry of Ca2+ binding changes from the usual two Ca2+ ions bound per ATPase molecule to one Ca2+ ion bound per ATPase molecule. For the ATPase in di(C24:1)PC, removal of Ca2+ from the Ca(2+)-bound ATPase results in a decrease in tryptophan fluorescence intensity, as observed for the ATPase in dioleoylphosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…For the ATPase in di(C ") : " )PC, removal of Ca# + from the Ca# + -bound ATPase results in a decrease in fluorescence intensity. For the ATPase in di(C "% : " )PC, removal of Ca# + results in an increase in fluorescence intensity in the presence of Mg# + , but no change in fluorescence intensity in the absence of Mg# + [40]. In mixtures of di(C "% : " )PC and either di(C ") : " )PS or di(C ") : " )PA, the fluorescence response to the removal of Ca# + gradually decreases in magnitude with an increase in the content of di(C "% : " )PC (results not shown), consistent with the gradual increase in activity to the maximum observed in Figure 6.…”
Section: Reconstitution With Mixtures Of Di(c 14 : 1 )Pc and Anionic mentioning
confidence: 97%
See 2 more Smart Citations
“…For the ATPase in di(C ") : " )PC, removal of Ca# + from the Ca# + -bound ATPase results in a decrease in fluorescence intensity. For the ATPase in di(C "% : " )PC, removal of Ca# + results in an increase in fluorescence intensity in the presence of Mg# + , but no change in fluorescence intensity in the absence of Mg# + [40]. In mixtures of di(C "% : " )PC and either di(C ") : " )PS or di(C ") : " )PA, the fluorescence response to the removal of Ca# + gradually decreases in magnitude with an increase in the content of di(C "% : " )PC (results not shown), consistent with the gradual increase in activity to the maximum observed in Figure 6.…”
Section: Reconstitution With Mixtures Of Di(c 14 : 1 )Pc and Anionic mentioning
confidence: 97%
“…Rapid kinetic and equilibrium binding experiments have shown that there is no one unique step in the reaction pathway of the Ca# + -ATPase that is sensitive to lipid structure, but rather that a number of different steps can be affected, with different changes in lipid structure affecting different steps. The Ca# + -binding sites on the ATPase are sensitive to the thickness of the phospholipid bilayer, reconstitution into bilayers of phosphatidylcholines containing short (C "% ) or long (C #% ) fatty acyl chains resulting in a change in the stoichiometry of Ca# + -binding to the ATPase [5,40]. However, changing the phase of the phospholipid from liquid crystalline bilayer to gel phase [32] or to hexagonal H II phase [33] has little effect on the Ca# + -binding sites.…”
Section: Mechanism Of Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, replacement of endogenous SR phospholipids by di-C16:0PC completely inhibits the Ca 2+ -ATP-ase activity at 4°C (gel phase), but not at 29°C (liquid-crystalline phase) [31]. Activities in phosphatidylethanolamines under conditions where the phos- phatidylethanolamine is in the hexagonal HII phase are also low [32]. Thus a liquid crystalline bilayer of the appropriate thickness with zwitterionic headgroups is required to stimulate Ca 2+ ATPase activity.…”
Section: Ca 2+ Atpasementioning
confidence: 99%
“…4 corresponds to the Ca2+-bound, E 1 conformation of the ATPase. It has been shown that the E1 conformation of the ATPase is favored by di(C14:1)PC, whereas di(C 18:1)PC favors the other major conformation of the ATPase, E2 (Starling et al, 1994). Thus, it is possible that conformational changes within the transmembrane region of the Ca2+-ATPase lead to changes in the interhelical loops and thus to changes in the effective hydrophobic thickness of the ATPase (Lee and East, 2001).…”
mentioning
confidence: 99%